A study on maintenance of air conditoning for agro-bio building / Muhammad Izwan Abdul Mutalib - Abdul Mutalib, Muhammad Izwan (Faculty of Architecture, Planning and Surveying, 2013)
Air conditioning maintenance for agro-bio building can be define as maintenance work carried out due to respect the design of agro-bio building. Biotechnology has many applications in agriculture, including diagnostics, vaccines and therapeutics for animal health. There are laboratory in agro-bio building that function as the research for biotechnology that must be design properly by following the standard of construction and design. The design of Agro-bio building also related to type of air conditioning system which mean that the design of the building must suitable with air conditioning system. The maintenance schedule of the building are different because it involve reaseach of argicultural development.(The National Biotechnology Division,2009). Objective of this study are study the air conditioning system installed with respect to design of Agro-bio building. Furthermore, this study also compared each air conditioning services available in agro-bio building to get the different due to maintenance management. Identify issues and problems that always occurs due to air conditioning system at Agro-bio building will help in maximize the performance of air conditioning maintenance for agro-bio. The result that air conditioning maintenance for agro-bio building shows that building design requirement is very important to maintenance work because it related to building design of agro-bio building. The maintenance work for air conditioning system must fulfil the requirement of agro-bio building because it is very important to make sure the building user is avoided to chemical and hazard in this building.